International Conference on Space Optics — ICSO 2016 2017
DOI: 10.1117/12.2296121
|View full text |Cite
|
Sign up to set email alerts
|

A compact frequency stabilized telecom laser diode for space applications

Abstract: We report on a Telecom laser diode (LD) frequency stabilization to a narrow iodine hyperfine line in the green range, after frequency tripling process using fibered nonlinear waveguide PPLN crystals. We have generated up to 300 mW optical power in the green range (~514 nm) from 800 mW of infrared power (~1542 nm), corresponding to a nonlinear conversion efficiency η = P3ω/Pω ~ 36%. Less than 10 mW of the generated green power are used for Doppler-free spectroscopy of 127 I2 molecular iodine, and -therefore-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A compact laser system for the stabilisation at 2051 nm (B2 line) using a HC-PCF filled with pure CO 2 was developed by Schilt et al [146], a relative frequency stability of 7 • 10 −10 is demonstrated for time scales ranging from 1 s up to 1000 s. More recently, a laser system based on NICE-OHMS instrumentation and frequency stabilisation on the acetylene 1531 nm and 1538 nm demonstrated relative frequency stability at the order of 10 −11 at 1 seconds of integration time, averaging down as 1/ τ up to 8 • 10 −13 at 240 s of integration time [147]. Finally, a laser system based on a frequency tripled Telecom laser diode at 1542 nm frequency stabilized to the narrow iodine hyperfine lines (at ≈ 514 nm) were reported by Philippe et al [148]. They used a 20-cm long multipass iodine cell and they demonstrate a relative frequency instability of 4.8 • 10 −14 averaging down as 1/ τ up to 6 • 10 −15 at 50 s. However, these two last publications do not present frequency stability at 1572 nm which result into a wavelength gap of 34 nm for [147] and 30 nm for [148].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A compact laser system for the stabilisation at 2051 nm (B2 line) using a HC-PCF filled with pure CO 2 was developed by Schilt et al [146], a relative frequency stability of 7 • 10 −10 is demonstrated for time scales ranging from 1 s up to 1000 s. More recently, a laser system based on NICE-OHMS instrumentation and frequency stabilisation on the acetylene 1531 nm and 1538 nm demonstrated relative frequency stability at the order of 10 −11 at 1 seconds of integration time, averaging down as 1/ τ up to 8 • 10 −13 at 240 s of integration time [147]. Finally, a laser system based on a frequency tripled Telecom laser diode at 1542 nm frequency stabilized to the narrow iodine hyperfine lines (at ≈ 514 nm) were reported by Philippe et al [148]. They used a 20-cm long multipass iodine cell and they demonstrate a relative frequency instability of 4.8 • 10 −14 averaging down as 1/ τ up to 6 • 10 −15 at 50 s. However, these two last publications do not present frequency stability at 1572 nm which result into a wavelength gap of 34 nm for [147] and 30 nm for [148].…”
Section: Discussionmentioning
confidence: 72%
“…Finally, a laser system based on a frequency tripled Telecom laser diode at 1542 nm frequency stabilized to the narrow iodine hyperfine lines (at ≈ 514 nm) were reported by Philippe et al [148]. They used a 20-cm long multipass iodine cell and they demonstrate a relative frequency instability of 4.8 • 10 −14 averaging down as 1/ τ up to 6 • 10 −15 at 50 s. However, these two last publications do not present frequency stability at 1572 nm which result into a wavelength gap of 34 nm for [147] and 30 nm for [148]. Moreover, long-term frequency instability for integration times longer than one day for a frequency stabilized laser at 1572 nm is abstent to our knowledge.…”
Section: Discussionmentioning
confidence: 98%